Біоекологічний аналіз метеликів родин Papilionidae, Pieridae і Nimphalidae міста Буська та його околиць - Теплюк, Вадим; Кубат, Наталія; Tepliuk, Vadim; Kubat, Natali (Східноєвропейський національний університет імені Лесі Українки, 2015)
У межах м. Буська та його околиць зареєстровано 31 вид денних метеликів із родин Papilionidae, Pieridae і Nimphalidae. Встановлено біотопічну приуроченість, трофічні зв’язки гусені, періоди льоту імаго, особливості зимівлі та розвитку окремих видів. The purpose of the work was to specify the species composition, to determine the relative abundance, to conduct a comprehensive bioecological analysis of day butterflies. The main natural habitats (forests, meadows) and agrocenoses were explored. 31 species butterflies were registered and they were divided into the groups depending on the relative abundance. Biotopical affiliation, trophic relations of caterpillars, flying period of adults, peculiarities of wintering and development of individual species were established. In meadows 24 species were registered and in the forests and agrocenoses there were 20 species in each. P. brassicae, P. rapae, P. napi, P. daplidice were marked as pests of agricultural crops in the caterpillar stage. The most of species (13) overwinters in larvae stage. The flying of butterflies begins from the middle of March and lasts until the middle of October. 17 species have one generation a year, 12 species have two, 2 species have more than two.
Bioecological analysis of Papilionidae, Pieridae and Nimphalidae butterflies families of the town Busk and its outskirts.
Keywords: метелики; гусінь; біотоп; ліси; агроценози; луки; butterflies; caterpillars; habitat; forests; grasslands; agrocenoses